The Influence of Narrow Reading on Reading Comprehension of the Eleventh Grade Students of SMAN 1 Srono in 2018/2019 Academic Year - Fatimatus Zhahrah; Tri Mulyati; Wulan Wangi (LUNAR, 2019)
The use of approach or strategy in teaching and learning process was needed to help EFL students in developing their four skills in English. One of the skills that needs to be developed is reading because reading activities include many things, one of which is reading comprehension. The aim of the research was to find the significant influence of narrow reading on reading comprehension of elevent grade students of SMAN 1 Srono in 2018/2019 academic year. The research design was experimental research and the researcher used one group pre-test and post-test design. Before giving a treatment, the respondents were given a pretest. Then the treatment was carried out for 3 meetings. After that the respondents were given test again as post-test. The researcher used purposive sampling to determine the research area. The reasearch area was SMAN 1 Srono. There were 35 students of elevent science 3 as respondents. It was taken by purposive sample. The data was obtained by using multiple choice test. There were 20 questions about topics, moral value, the characteristics, plot of story, the purpose of narrative text and vocabulary, finding synonim and references. The results of T-test showed that there was significant influence on students’ reading comprehension abilities. The value of T-test was 6,674, while the value of T table at the significant level of 5% and degree of freedom 33 was 2,012. It means that the value of T-tes was higher than the value of T table (6,674 > 2,012). Therefore it can be concluded that the narrow reading had significant influence on reading comprehension of elevent grade students of SMAN 1 Srono in 2018/2019 academic year. Based on the results of T-test, the researcher suggested to the English teacher to apply the narrow reading approach in the reading class to make students are more interested and enjoyable to study. The other reseracher are suggested to do the same research with different grade students, school and research design and use the other genres. It is recommended to make experimental research using two group, experimental group and control group.